(untitled) - 1967-; Toro, Benicio del; Oz, Frank; Dern, Laura; Williams, John; Tran, Kelly Marie; 1978-; 1932-; Ducsay, Bob; Yedlin, Steve; Kaplan, Michael; (Costume designer); et al. (Burbank, California, 2018)
The Skywalker saga continues as the heroes of The Force Awakens join the galactic legends in an epic adventure. Having taken her first steps into the Jedi world, Rey joins Luke Skywalker on an adventure with Leia, Finn and Poe that unlocks mysteries of the Force and secrets of the past.
Keywords: Drama; (Fictitious character); Solo, Han; Drama; (Fictitious character); Organa, Leia; Drama; (Fictitious character); Skywalker, Luke; Drama; Robots; Drama; Good and evil; Drama; Drama; Drama; Life on other planets; Jedi (Fictitious characters); Space warfare; Feature films; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Action and adventure films; Science fiction films; Fiction films